Réponses

2014-03-26T17:41:38+01:00
1) x² - 4x + 4 = (x - 2)² c'est une identité remarquable donc :
x² - 4x + 4 = (3x + 5)(x - 2) ⇔ (x - 2)² = (3x + 5)(x - 2)
⇔ x - 2 = (3x + 5)(x -2)/(x-2)
⇔ x - 2 = 3 x + 5
⇔ 2x = -7
⇔ x = -7/2

2) 4/3-2x ≥ 3/2+x/3 ⇔ -2x - x/3 ≥ 3/2 - 4/3
⇔ -6x/3 - x/3 ≥ 9/6 - 8/6
⇔ -7x/3 ≥ 1/6
⇔ -7x ≥3/6
⇔ -x ≥ 3/56 ⇔ x≤ 3/56 (on change le signe de x donc le sens de l'inégalité)
2014-03-26T19:39:00+01:00
1) x² - 4x + 4 = (x - 2)² c'est une identité remarquable donc :
x² - 4x + 4 = (3x + 5)(x - 2) ⇔ (x - 2)² = (3x + 5)(x - 2)
 x - 2 = (3x + 5)(x -2)/(x-2)
 x - 2 = 3 x + 5
 2x = -7
 x = -7/2
2) 4/3-2x ≥ 3/2+x/3 ⇔ -2x - x/3 ≥ 3/2 - 4/3
 -6x/3 - x/3 ≥ 9/6 - 8/6
 -7x/3 ≥ 1/6
-7x ≥3/6
voila s galere les maths